Tuning of superconducting cavities using the FFT of transmitted power. Issue 1 (1st January 2023) - Laface, E; Maiano, C G; Pierini, P; Wang, M
Abstract: We implemented a method to tune the ESS superconducting cavities based on the spectral analysis of the high resolution data available from the Low Level RF system (LLRF) for the transmitted power, without the need of connecting a network analyzer or any other dedicated instrumentation along the RF chain. A frequency peak up to 4 MHz off from the resonating frequency can be detected and used to control the stepper motor of the tuner until the cavity is stretched to the proper length to reach the correct operation frequency. Experience of its use at the ESS Test Stand 2 (TS2) facility at Lund during cryomodule acceptance testing is presented.